Analisis Sistem Kompensasi Berdasarkan Salary Mapping Adhered dan Overlapping Pada Ukm Xyz - Ahmad Nagib; Kevin Pratama Nafis; Lindawati Kartika; Muhammad Adlin Radhitya Fadlan; Muhammad Ihsan Almunawar; Rafi Gibran Priatna Junior (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
This study examines the compensation system at SME XYZ, focusing on adhered and overlapping salary mapping. The primary goal of this research is to analyze and evaluate the existing compensation structure and provide recommendations for improvement. The methodology used includes collecting primary data through interviews and questionnaires, and secondary data analysis from previous studies. The findings indicate that the salary structure at SME XYZ is not optimal, with some positions being paid below the Bandung City minimum wage standard. Further analysis revealed that implementing an overlapping salary structure method can improve internal fairness and employee satisfaction without significantly increasing the company's financial burden. This study suggests that SME XYZ adopts a more flexible and fair salary structure, considering employee capabilities and contributions as well as local labor market conditions.